Comparative Sensitivity of Human Acetylcholinesterase to in vitro Inhibition by Synthetic Analogues of Phosphoramidate Compounds - Mahmoudi, Ali; Dehghanpour, Saeed; Jahani, Khadijeh; Rasmi, Yousef (Asian Journal of Chemistry, 2010)
Using phosphoryl chloride as a substrate, some phosphoramidate derivatives with the general formula (R1)(O)PCl(R2); [R1 = NMe2, OC6H5, OC6H4CH3 and R2 = N(CH2C6H5)(CH3), N(CH2C6H5)(C2H5)] was prepared and characterized by 1H, 31P and 13C NMR and IR spectroscopy and elemental analysis. Biochemical studies conducted to evaluation of sensitivities of human acetylcholinesterase to inhibition of these compounds. Determination of human erythrocyte acetylcholinesterase (hAChE) activity was carried out according to the Ellman’s modified kinetic method. Biomolecular rate constant (ki) of the selected compounds towards the active site of hAChE ranged between 2.4 × 10-3 and 5.23 × 10-1 M-1 min-1 and their IC50 values varied from 2.33 × 10-1 to 1.99 × 10-3 mM. The difference in the inhibitory potency of these compounds is discussed with respect to their hydrophobicity. A comparison of the ki and IC50 values for inhibition of hAChE by these inhibitors revealed that hydrophobic, steric and electronic factor of phosphorus substituents are important in potency of inhibitory on hAChE.